Inventarisasi, Hubungan Kekerabatan, dan Pemanfaatan Bambu (Poaceae: Bambusoideae) di Kawasan Hutan Desa Tompobulu Kabupaten Pangkep - Astina Astina; Gaby Maulida Nurdin; Alin Liana (Fakultas MIPA UNM, 2022)
Abstract. An inventory of bamboo species in various regions is carried out to explore its potential in the local community so that each type can be utilized and conserved optimally. This study aims to determine the types of bamboo found in Tompobulu Village, the status of kinship between species, and the benefits of bamboo for people's lives. Exploration has been carried out using the tracking method. The species found were identified morphologically on the culm, culm sheath, branches, and leaves. Data were analyzed quantitatively using cluster analysis with UPGMA. PCA was used to determine the role of each morphological character in accession grouping. This study identified eight bamboo species from five genera, namely Bambusa striata, B. vulgaris, Dendrocalamus asper, Gigantochloa atter, Gigantochloa sp., Schizostacyum brachycladum, Schizostacyum sp., and Nastus sp. The kinship dendrogram shows the cluster separation between Nastus and Schizostacyum with Bambusa, Dendrocalamus, and Gigantochloa. All species identified have been used by the community, Gigantochloa atter has the most benefits than other types of bamboo. The results of this study further enrich the biodiversity of bamboo in Indonesia and strengthen the current taxonomic position of bamboo.Keywords: bamboo, bulusaraung mountain, inventory, pangkep, tompobulu village